Has adult sleep duration declined over the last 50+ years?. (August 2016) - Youngstedt, Shawn D.; Goff, Eric E.; Reynolds, Alexandria M.; Kripke, Daniel F.; Irwin, Michael R.; Bootzin, Richard R.; Khan, Nidha; Jean-Louis, Girardin
Summary: The common assumption that population sleep duration has declined in the past few decades has not been supported by recent reviews, which have been limited to self-reported data. The aim of this review was to assess whether there has been a reduction in objectively recorded sleep duration over the last 50+ years. The literature was searched for studies published from 1960 to 2013, which assessed objective sleep duration (total sleep time (TST)) in healthy normal-sleeping adults. The search found 168 studies that met inclusion criteria, with 257 data points representing 6052 individuals ages 18–88 y. Data were assessed by comparing the regression lines of age vs. TST in studies conducted between 1960 and 1989 vs. 1990–2013. Weighted regression analyses assessed the association of year of study with age-adjusted TST across all data points. Regression analyses also assessed the association of year of study with TST separately for 10-y age categories (e.g., ages 18–27 y), and separately for polysomnographic and actigraphic data, and for studies involving a fixed sleep schedule and participants' customary sleep schedules. Analyses revealed no significant association of sleep duration with study year. The results are consistent with recent reviews of subjective data, which have challenged the notion of a modern epidemic of insufficient sleep.